2017
DOI: 10.3389/fpsyg.2017.01634
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Health in the Retirement Transition: Rationale and First Findings in the HEalth, Ageing and Retirement Transitions in Sweden (HEARTS) Study

Abstract: From an aging research and life-course perspective, the transition to retirement marks a significant life-event and provides a unique opportunity to study psychological health and coping during a period of substantial change in everyday life. The aim of the present paper is to: (a) outline the rationale of the HEalth, Ageing and Retirement Transitions in Sweden (HEARTS) study, (b) describe the study sample, and (c) to present some initial results from the two first waves regarding the association between retir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 65 publications
3
75
1
Order By: Relevance
“…In addition, survey respondents may have a different definition of their retirement age than the researchers, or the definition may even differ between respondents with similar transition to retirement (Cahill et al 2015). An advantage of using self-reported retirement is that the respondents' subjectively perceived status is assessed, which might be a better assessment of one's own perception and identity of retirement status than the objective drop in income or number of hours worked (Denton and Spencer 2009;Lindwall et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, survey respondents may have a different definition of their retirement age than the researchers, or the definition may even differ between respondents with similar transition to retirement (Cahill et al 2015). An advantage of using self-reported retirement is that the respondents' subjectively perceived status is assessed, which might be a better assessment of one's own perception and identity of retirement status than the objective drop in income or number of hours worked (Denton and Spencer 2009;Lindwall et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This allows for better estimation of the respondent's own perception of her retirement transition. Researchers using the HEARTS survey have, based on the item above, applied their own definition of retirement that fit with the objective of the study (Hansson et al 2018;Henning et al 2017;Lindwall et al 2017). In the Swedish Longitudinal Occupational Survey of Health (SLOSH), participants are asked to respond to the most appropriate questionnaire for their current work situation: the one for people working 30% or more of full time during the past 3 months or the one for people who were less than 30% gainfully employed in the past 3 months .…”
Section: Definition Of Retirement Age In Studies Using Swedish Datamentioning
confidence: 99%
“…The topic remains controversial as the association between health and labor market participation is affected by different factors, such as the sector of activity, level of education, financial wealth, gender, the size of the company and the socio‐economic status . For instance, looking at longitudinal data from Sweden, Lindwall et al have pointed out that more positive changes in psychological health are observed for respondents who retired compared with those still working. Looking at self‐rated health using the French GAZEL cohort, it has been shown that retirement leads to a sustainable retirement‐related improvement in self‐rated health, both for men and women and across occupation grades .…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have demonstrated variability in the reaction to retirement (Pinquart & Schindler, 2007;Wang, 2007), highlighting the need to examine the course of depressive symptoms in a way that enables the study of groups with differing trajectories of depressive symptoms (Andreescu, Chang, Mulsant, & Ganguli, 2008;Henning, Lindwall, & Johansson, 2016;Lindwall et al, 2017). Groupbased trajectory models allow study of such heterogeneity (Nagin, 1999(Nagin, , 2005.…”
Section: Introductionmentioning
confidence: 99%